Aspects of social interactions of HIV-positive children from the perspective of their caregivers - Marli Teresinha Gimeniz Galvão; Gilmara Holanda da Cunha; Naya Lúcia de Castro Rodrigues; Elucir Gir (Universidade Federal do Ceará, 2013)
The occurrence of HIV-infected women resulted in the birth of children exposed or infected by the virus. This research aimed to identify aspects of HIV-positive children's interactions. This exploratory and descriptive study of qualitative approach was developed at an HIV/AIDS care referral service in Fortaleza-CE, Brazil, between July and December 2009. Participants were caregivers of 13 children infected with HIV. The semi-structured interviews and content analysis enabled the creation of categories: fear of contamination by HIV in the family core; lack of confidentiality and training of health professionals in care delivery to HIV/AIDS patients; and social exclusion in the family, neighborhood and school environment. In conclusion, the social interactions of HIV-positive children are impaired. Fear, exclusion and prejudice permeate the caregivers' lives, due to the fear that the children will be discriminated against in society. This study reveals information that can support holistic nursing care.